THE SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF ADULT LEARNING AND DEVELOPMENT - Zichenko, S.; Kotirlo, T. (Main Issues Of Pedagogy And Psychology, 2017)
The authors consider the problem of the adult social and psychological development and education. It analyzes various directions of social and psychological development, the peculiarities of the institutional type of training, as well as the basis of forms oftraining of adult education.